2019
DOI: 10.25163/angiotherapy.21206512012110519
|View full text |Cite
|
Sign up to set email alerts
|

Anti-GBM potential of Rosmarinic acid and its synthetic derivatives via targeting IL17A mediated angiogenesis pathway

Abstract: Glioblastoma (GBM) is a highly angiogenic malignant primary brain tumor with very poor patient survival rates. Here, we present Rosmarinic acid and its new salt and base derivatives that show potential anti-glioblastoma (anti-GBM) activity via disruption of IL17A-mediated downstream angiogenesis pathway. These new compounds were rationally designed, synthesized and the oral CNS physicochemical properties were determined. The anti-GBM activity of the compounds were determined using cell migration and proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Previous studies on the effect of RA in brain cancer cell lines have shown different sensibility to the compound. In the glioblastoma cell line U-87 MG, the estimated IC 50 following 72 h RA-exposure was 40 μM (Khan et al 2019). Using the same cell line and a 48h RA-treatment protocol, the estimated IC 50 was 373.48 μM (Şengelen and Önay-Uçar 2018).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies on the effect of RA in brain cancer cell lines have shown different sensibility to the compound. In the glioblastoma cell line U-87 MG, the estimated IC 50 following 72 h RA-exposure was 40 μM (Khan et al 2019). Using the same cell line and a 48h RA-treatment protocol, the estimated IC 50 was 373.48 μM (Şengelen and Önay-Uçar 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Studies have previously demonstrated that RA can modulate HDAC expression (Ferdousi et al 2019;Jang et al 2018) and EGFR activity (Balogun et al 2021;Tumur et al 2015), which are targets for MB therapies. Although its antitumor effects against other types of central nervous system (CNS) cancer cell lines have been demonstrated (Khan et al 2019;Ramanauskiene et al 2016;Şengelen and Önay-Uçar 2018), previous studies have not examined its possible effects in MB models.…”
Section: Introductionmentioning
confidence: 99%
“…FLVM also showed an immunomodulatory effect on GBM TME. Both molecules downregulated HIF-1α, reducing hypoxia in the GBM tissue and promoting its apoptosis by increasing the levels of reactive oxygen species [ 72 , 98 ].…”
Section: The Role Of Il-17 and Th17 Immunity In The Treatment Of Gbm-...mentioning
confidence: 99%